Megafauna decline have reduced pathogen dispersal which may have increased emergent infectious diseases - Doughty, Christopher E.; Prys-Jones, Tomos O.; Faurby, Søren; Abraham, Andrew J.; Hepp, Crystal; Leshyk, Victor; Fofanov, Viacheslav Y.; Nieto, Nathan C.; Svenning, Jens-Christian; Galetti, Mauro [UNESP] (Wiley, 2020)
The Late Quaternary extinctions of megafauna (defined as animal species > 44.5 kg) reduced the dispersal of seeds and nutrients, and likely also microbes and parasites. Here we use body-mass based scaling and range maps for extinct and extant mammal species to show that these extinctions led to an almost seven-fold reduction in the movement of gut-transported microbes, such as Escherichia coli (3.3–0.5 km2 d−1). Similarly, the extinctions led to a seven-fold reduction in the mean home ranges of vector-borne pathogens (7.8–1.1 km2). To understand the impact of this, we created an individual-based model where an order of magnitude decrease in home range increased maximum aggregated microbial mutations 4-fold after 20 000 yr. We hypothesize that pathogen speciation and hence endemism increased with isolation, as global dispersal distances decreased through a mechanism similar to the theory of island biogeography. To investigate if such an effect could be found, we analysed where 145 zoonotic diseases have emerged in human populations and found quantitative estimates of reduced dispersal of ectoparasites and fecal pathogens significantly improved our ability to predict the locations of outbreaks (increasing variance explained by 8%). There are limitations to this analysis which we discuss in detail, but if further studies support these results, they broadly suggest that reduced pathogen dispersal following megafauna extinctions may have increased the emergence of zoonotic pathogens moving into human populations.
Keywords: emergent infectious diseases; extinctions; megafauna